PENGARUH ARUS KAS KEGIATAN OPERASI, SIKLUS OPERASI, UKURAN PERUSAHAAN DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA (STUDI EMPIRIS PADA PERUSAHAAN JASA SUB SEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016) - Sarah, Varadika; Jibrail, Ahmad; Martadinata, Sudrajat (Jurnal TAMBORA, 2019)
Earnings Persistence is earning can reflect the earnimg priod next. In fact there are still companies that do not guarantee a persistent of earning. This study wished to examine ehe effect of operating cash flows, operating cycle, firm size, and the lever of debt both individually and simultaneously to earning persistence in service compnies of construction and building sector listed on Indonesia Stock Exchange period 2013-2016. The sampling technique using purposive sampling so than 9 sample companies were obtained. Data were analized using panel data with multiple regression then tested with the help of STATA 11 softwere.The result of this study are: operating cash flow, operating cycle, firm size there is not significant effect on earning persistence. While the level of debt has significant effect on earning persistence in service compnies of construction and building sector listed on Indonesia Stock Exchange period 2013-2016